2017
DOI: 10.4236/fns.2017.81010
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Stilbene Antioxidants of the Bio-Elicited Peanut Sprout Powder (BPSP) and Longevity Extension of Mice Fed with BPSP-Supplemented Diets

Abstract: Biosynthesis of peanut stilbenes, including resveratrol as the secondary metabolites, could be enhanced by subjecting the kernels to germination and wound-stress. Investigations of the bio-elicited peanut sprout powder (BPSP) addressed on characterization of the comprising stilbenes and effectiveness in longevity extension deserves intensive research. In this study, peanut kernels were subjected to germination and wound-stress in preparation of BPSP. The methanol extracts of BPSP were medium pressure liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, a recent study revealed that mice that were daily fed bio‐elicited peanut sprout powder that contained stilbenes at a dose of 0.5‐g/kg body weight for 762 days did not have any toxicity‐related health risks. The results reveal that mice had extended longevity, suggesting that it could be attributed to the antioxidant and antiglycative properties of stilbenes (Chiou et al, ). This demonstrated the safety of stilbenes in food preservation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study revealed that mice that were daily fed bio‐elicited peanut sprout powder that contained stilbenes at a dose of 0.5‐g/kg body weight for 762 days did not have any toxicity‐related health risks. The results reveal that mice had extended longevity, suggesting that it could be attributed to the antioxidant and antiglycative properties of stilbenes (Chiou et al, ). This demonstrated the safety of stilbenes in food preservation.…”
Section: Resultsmentioning
confidence: 99%
“…However, these food additives are associated with safety problems. Regarding the safety of stilbenes, a recent study revealed that stilbenes were not toxic and extended longevity in mice that were fed stilbenes on a daily basis (Chiou et al, ). Thus, this study aimed to evaluate the antibacterial and antioxidant properties of stilbenes in peanuts extracts and assess whether stilbenes are potential preservatives for sausage products.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments respectively conducted with aged BALB/c and ICR mice BPSP-supplemented diets daily for 750 and 762 days in the doses of 0.1 and 0.5 g BPSP/kg BW had average ca. 30% extension on lifespan longer than the mock groups (Chiou et al 2017). Accordingly, the reduced allergenicity and food toxicological acceptance of BPSP gives merit to pursuing BPSP as a novel food ingredient.…”
Section: Relative Organ Weight and Histopathological Examinationmentioning
confidence: 99%
“…If sorted and sound peanut kernels are used through natural methods and without the use of any chemical, there is less toxicological concern. Peanut sprouts and defatted germinated peanut powder have been demonstrated to be safe and of benefit to human health (Lin et al, ; Chiou et al, ). Moreover, when peanuts are soaked and allowed to germinate, their glyoxylic acid cycle converts their fat into carbohydrates, and the key enzyme of this cycle is isocitrate lyase (ICL).…”
Section: Introductionmentioning
confidence: 99%
“…Then, cotyledons are removed and subjected to machine slicing, followed by fast and consistent dehydration. During the slicing and spreading required to dehydrate the slices, the live tissue slices are still producing resveratrol as well as other stilbenoids (Chang et al, ; Chiou et al, ). After the peanuts have been cultivated at an optimal germination temperature of 30 °C for 4 days, high‐performance liquid chromatography (HPLC) can be used to map the products and resveratrol content.…”
Section: Introductionmentioning
confidence: 99%